2013
DOI: 10.1097/adm.0b013e318283698c
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine Normalization of Workplace Urine Drug Tests

Abstract: This result indicates that specimen dilution does affect the number of laboratory-positive results confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…However, for each drug, the post-normalization positivity rate was increased compared with the pre-normalization rates (Table 4). This finding is in agreement with the study by , which showed an increase in positivity rates for each drug examined after normalization [5].…”
Section: F I G U R E 6 Urine Specimen Collection Time and Mean Cr Concentrations (With Sd)supporting
confidence: 93%
See 1 more Smart Citation
“…However, for each drug, the post-normalization positivity rate was increased compared with the pre-normalization rates (Table 4). This finding is in agreement with the study by , which showed an increase in positivity rates for each drug examined after normalization [5].…”
Section: F I G U R E 6 Urine Specimen Collection Time and Mean Cr Concentrations (With Sd)supporting
confidence: 93%
“…Nevertheless, dilution affects the results of tests for illegal substances. Normalization of urinary drug concentrations by urine creatinine levels may augment the effectiveness of deterrent programs by mitigating volitional in vivo dilution as a means of subverting urinary drug test results [5].…”
Section: F I G U R E 6 Urine Specimen Collection Time and Mean Cr Concentrations (With Sd)mentioning
confidence: 99%
“…In this study, we analyzed potential urinary biomarkers of 18 DDKT recipients and revealed that the urinary levels of TG2 tended to be higher and that of SDC4 tended to be lower when IFTA was aggravated at the 6-month allograft biopsy. Urine molecule concentration depends on several biological variables such as fluid intake, body composition, in addition to hepatic and renal functions [29]. Since urinary creatinine concentration serves as an indicator of urine dilution, we measured the level of urine creatinine and mathematically adjusted for creatinine normalization of TG2 and SDC4 by dividing each concentration by the urine creatinine level.…”
Section: Discussionmentioning
confidence: 99%
“…This is an observational study at a single institution evaluating a relatively small number of patients. Furthermore, a common challenge of protein analysis of spot urine samples collected involves differences in the abundance of each protein or metabolite in biological fluids and the concentration of biological fluids is affected by various factors and by the physiological status of the patients [29]. There are several cases with missing data of urinary biomarker levels which may have possibly influenced the small cohort sample present in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Urine molecule concentration depends on several biological variables such as fluid intake, body composition, hepatic function, and renal function 16. Because urinary creatinine concentration serves as an indicator of urine molecule concentration level, we measured the level of urine creatinine.…”
Section: Methodsmentioning
confidence: 99%